Preparation, characterization and catalytic performance of Ag/Ce/La co-modified TiO2 photocatalysts. (2nd January 2018) - Zi-shang, Chen; Xiao-ping, Liang; Shuang-yuan, Zhu; Di, Zhang; Shan-min, Yang; Xiao, Yao; Jia-qi, Zhao; Huang-ying, Wang; Jian-xin, Li
ABSTRACT: Ag and rare earth elements (Ce-La) co-modified TiO2 photocatalysts were synthesized via sol–gel method. The structure of co-modified TiO2 was investigated by using TEM, XRD, XPS and UV–visible absorption spectra. Based on the ammonia nitrogen degradation experiment, the effects of the co-modifier content (1, 3, 5wt% Ag/Ce/La) on the photocatalytic activity of TiO2 were evaluated systematically. The results showed the crystal phase of modified TiO2 transformed from anatase/rutile mixture to pure anatase, and the anatase crystallites size decreased after co-modifying. Ag was deposited onto the surface of TiO2 photocatalyst, and the synergistic effect of Ce-La and Ag caused the decrease of band gap energy from 3.2 eV to 2.0 eV. In the degradation of ammonia nitrogen wastewater, 3% Ag/Ce/La-TiO2 photocatalyst represented the best activity, whose degradation efficiency of ammonia nitrogen reached 93.9% after 6 h degradation reaction, whereas was 27.8% in case of pure TiO2 .